Environmental trade-offs of pig production systems under varied operational efficiencies. (1st November 2017) - McAuliffe, G.A.; Takahashi, T.; Mogensen, L.; Hermansen, J.E.; Sage, C.L.; Chapman, D.V.; Lee, M.R.F.
Abstract: Production of pork, the most consumed meat globally, is estimated to emit 668 m tonnes CO2 -eq of greenhouse gases each year. Amongst various production systems that comprise the pig industry, grain-based intensive production is widely regarded as the largest polluter of the environment, and thus it is imperative to develop alternative systems that can provide the right balance between sustainability and food security. Using an original dataset from the Republic of Ireland, this paper examines the life-cycle environmental impacts of representative pig farms operating under varying production efficiencies. For the baseline farm with an average production efficiency, global warming potential (GWP), acidification potential (AP) and eutrophication potential (EP) per kg carcass weight departing the slaughterhouse were estimated to be 3.5 kg CO2 -eq, 43.8 g SO2 -eq and 32.1 g PO4 -eq, respectively. For herds with a higher production efficiency, a 9% improvement in feed conversion ratio was met by 6%, 15% and 12% decreases in GWP, EP, AP, respectively. Scenario and sensitivity analyses also revealed that (a) a switch to high-protein diets results in lower GWP and higher AP and EP, and (b) reducing transportation distances by sourcing domestically produced wheat and barley does not lower environmental impacts in any notable manner. To improve cross-study comparability of these findings, results based on an auxiliary functional unit, kg liveweight departing the farm gate, are also reported. Highlights: Environmental footprints of Irish commercial pig production systems were examined. Dual-functional unit approach was adopted to enhance cross-study comparability. Trade-offs were identified between global warming and acidification/eutrophication. 'Feed mileage' was found to have little impact on environmental performance. Economic and environmental performances were shown to be positively correlated.